EMERGING TECHNOLOGIES APPLIED IN THE EXTRACTION OF DIETARY FIBER FROM AGRICULTURAL WASTE: SYSTEMATIC REVIEW - Malpartida Yapias, Rafael Julián (2023)
This article identifies studies conducted on the extraction of dietary fiber from agricultural residues. The systematic review was applied in two databases SCOPUS and Science direct, applying keywords in English. The total search showed 308 papers, from which data have been filtered and excluded, resulting in ten fundamental researches on extraction from ultrasound and microwave extraction methods, allowing to identify the impact of dietary fiber extraction methods focusing on the revaluation of agricultural residues for food, biotechnological and pharmaceutical use.